Una metodología eficiente para manejo de restricciones en algoritmos evolutivos multi-objetivo - Echeverri, Mauricio Granada; López Lezama, Jesús María; Romero, Ruben [UNESP] (My University, 2009)
This paper presents a new approach for solving constraint optimization problems (COP) based on the philosophy of lexicographical goal programming. A two-phase methodology for solving COP using a multi-objective strategy is used. In the first phase, the objective function is completely disregarded and the entire search effort is directed towards finding a single feasible solution. In the second phase, the problem is treated as a bi-objective optimization problem, turning the constraint optimization into a two-objective optimization. The two resulting objectives are the original objective function and the constraint violation degree. In the first phase a methodology based on progressive hardening of soft constraints is proposed in order to find feasible solutions. The performance of the proposed methodology was tested on 11 well-known benchmark functions.
An efficient constraint handling methodology for multi-objective evolutionary algorithms
Keywords: Constraint optimization; Evolutionary algorithms; Multi-objective algorithms